Siat Yeh : an appreciation to water source – Cultural Tradition in Jimbaran and Gianyar - Ida Bagus Gede Putra (Bali Tourism Journal, 2020)
Balinese daily life is closely related to spiritual practices as a religious society. Various traditions are held on the island closely associated with their religious life, Whether it is a piodalan series at a temple or in a series of Hindu religious holidays. Every area has its distinguished ways of expressing gratitude to the higher being. one of them is the Siat Yeh, a tradition common in Banjar Teba, Jimbaran and Suwet Village, Gianyar. Balinese people interpret water as a source of life. The spirit of water conservation has been passed down through various ritual activities, including the Siat Yeh activities in Jimbaran and Suwat Village. The Siat Yeh tradition in Banjar Teba, Jimbaran, was an ancient tradition that the residents had revived. It is expected that the meeting of two holy water sources from Suwung Beach and Segara Beach would bring prosperity to the residents. People believe by meeting these two sacred waters would bring positive energy for them. Aside from a symbol of respect for the two holy water sources, the people of Banjar Teba hope that Siat Yeh will become a legacy that can be passed on to future generations. The villagers of Suwat, Gianyar, also carry out similar Water war activities. Albeit different in some of its technical processes, this hereditary tradition is also a means to worship ancient water sources that have previously supported community survival and hitherto. This activity has become an annual event that has successfully attracted the attention of many visitors to participate. Its simple activities are the primary reason many tourists were interested in seeing this cultural heritage.